Sustaining our future through youth education - Bronleewe, Tonya (Kansas State University, 2009)
In order for today's young people to be adequately informed, educated, and prepared for adulthood they need to understand both local and global natural resources, and the issues that surround them. Every decision from simple lifestyle choices, which type of car to purchase, to global policy making, is there enough drinking water to sustain the world's growing population, has environmental consequences that are becoming increasingly significant. Unfortunately, most schools and communities do not have resources, expertise or time to plan effective, comprehensive, research-based programs that help young people become aware and active in environmental issues. Kansas State University Research and Extension is addressing youth environmental education needs on a statewide level through a school-based program for middle and high school students. With help from the Kansas Department of Health and Environment's Bureau of Water, the Earth Awareness Researchers for Tomorrow's Habitat (E.A.R.T.H) project equips teachers and community volunteers throughout the state with the resources needed to provide effective, hands-on education for their students and communities. The E.A.R.T.H. program is designed to introduce students to environmental issues in the areas of air, water, soil, living resources, and impacts. Teachers receive curriculum, supplies, and training in order to empower students with skills and knowledge to identify, prevent, and/or solve local and global environmental problems. At the end of each year, students attend a Workshop where they are put in contact with local environmental experts who provide real world applications to their in-class environmental studies. During this presentation attendees will explore the significance and take part in a hands-on natural resource education lesson. Then, the focus will turn to practical ways to bring authentic, hands-on environmental education into any school or community in ways that satisfy the educational standards that every educator is required to accomplish. Research shows that 90% of students will remember and be able to apply skills and knowledge that are experienced; only 10-15% remembers things they have only read or heard. This presentation will explore the resources available to help schools and communities to provide youth with unforgettable experiences that promote sustainability for Kansas’ natural resources.
Keywords: Natural resources; Earth Awareness Researchers for Tomorrow's Habitat (E.A.R.T.H.); Environment; Environmental education; Youth; Impacts; Science education